Contrastive Analysis, Transfer Analysis, Error Analysis, And Interlanguage: Four Concepts One Goal - Endang Fauziati (Ahmad Dahlan Journal of English Studies, 2014)
AbstractContrastive Analysis, Transfer Analysis, Error Analysis, and Interlanguage are methods used for second language learning investigation. They constitute evolutionary phases in the attempt to understand and explain the nature of the target language learners' performance. Each theory has its own view, especially in the attitude toward learners' errors and the explanatory hypotheses regarding the sources of errors. They also appear to have one goal, that is, an attempt to facilitate the process of target language learning or teaching by studying learners' errors. They are complement to one another; they constitute four phases with one goal.Contrastive analisis aims to provide teachers and/or textbook writers with information that can be utilized in the preparation of instructional materials, the planning of courses, and the development of classroom techniques. Contranstive studies are carried out in order to describe the differences between learners' native language amd the target language. They believe that it is on these differences that the learning difficulties lie, consequently errors exist. Transfer analysis is a new lebel given to contrastive analysis. Other sister terms are language transfer and crosslinguistic influence. This is an analytical tool which constitutes a sub discipline within error analysis. Its basic assumption is that certain errors in learner performance are the result of native language transfer. Error Analisis disproves the predictions of theory lying behind the comparison of native language and target language. It is an experimental technique for validating the theory of transfer. Its goal is to find out something about the psycholinguistic process of language learning. It enables us to draw a certain conclusions about the strategies used by the learner in his learning process. Interlanguage is a popular term to refer to learners' versions of the target language. It usually contains elements of both the learners' native language and target language. Interlanguage is resulted from the learner's attempts to produce the target language construction. In other words, it is the product of the second language learning process.